Humanistic Supervision and Collaborative Governance Model of Madrasah Principals in Handling Dual Indiscipline in Pesantren - Kamal Agung Wijaya (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2026)
Enforcing discipline in madrasahs located within pesantren environments often faces the complex challenge of dual indiscipline involving both teachers and students. This study aims to analyze in depth the role of the madrasah principal as a supervisor in handling teacher and student discipline problems at Pondok Pesantren Nurul Amin, Samarinda. Utilizing a qualitative approach with a descriptive case study design, data were gathered through in-depth interviews, limited participant observation, and documentation involving the principal, teachers, and students. Data analysis followed the interactive model of Miles, Huberman, and Saldaña. The results indicate that the principal executes a three-stage operational framework for disciplinary supervision: adaptive planning, direct monitoring implementation, and cross-sectoral follow-up evaluation. The intervention employs a humanistic and value-based approach through coaching, spiritual role modeling, and servant leadership. Institutional bottlenecks, particularly time constraints due to excessive administrative workloads, are effectively mitigated through collaborative governance strategies, delegating tasks to senior teachers, and strengthening coordination with dormitory management. In conclusion, a professional and collaborative supervisory role by the madrasah principal is key to fostering a sustainable culture of discipline within the pesantren ecosystem.